Does senescence affect lymph node number and morphology? A systematic review. Issue 9 (25th January 2013) - Ahmadi, Omid; McCall, John L.; Stringer, Mark D.
Abstract: Background: Immunosenescence may contribute to an observed increase in infections and specific cancers in the elderly. Lymph nodes play a key role in the body's immune system. A systematic review was undertaken to investigate the effects of senescence on lymph node number and morphology. Methods: Electronic databases Ovid MEDLINE, Embase and Google Scholar were searched for relevant articles examining normal lymph node number and morphology with senescence. Data on lymph node number, gross anatomy and histo‐architecture were collated and analysed. Results: A total of 20 articles (15 human and 5 animal studies) were eligible for inclusion; many were limited by poorly standardized methods and relatively small sample sizes. However, there is evidence to suggest both a decrease in lymph node number and histological lymph node degeneration with senescence, at least in some lymph node basins. Degenerative changes include loss of lymphoid tissue from both the cortex and the medulla of lymph nodes, a reduction in the number and size of germinal centres, and changes such as hyalinization, fibrosis, fat deposition, a decrease in high endothelial venules and 'transparency'. Conclusion: In this first systematic review to examine changes in lymph nodes with senescence, evidence was accrued to suggest a decline in lymph node number and morphological degeneration in older age groups. These changes might adversely affect immune function and the prognosis of infections and selected cancers in the elderly. Further research is required to confirm these morphological changes and to explore their potential immunological and functional effects.